Multiple impacts of invasive species on species at risk: a case study in British Columbia, Canada - Natascia Tamburello; M. Aline Litt (Canadian Science Publishing, 2023)
Invasive species are a leading cause of biodiversity loss and species extinctions across ecosystems on a global scale. The historical and ongoing focus on single-species management of invasive species and species at risk contributes to inefficiencies in management strategies that present an obstacle to achieving desired outcomes. A holistic approach that consolidates and maps linkages between the broader collective of invasive species and species at risk in an area provides a more appropriate entry point for issue-based, rather than species-based, management planning. We present a case study of this approach from British Columbia, Canada, which synthesized the identity, mechanisms of impact, mechanisms of spread, and magnitude of impacts across 782 unique pairs of invasive species and federally listed species at risk, based on a literature review of species at risk documentation. The resulting dataset was used to summarize the nature of interactions across species pairs and taxonomic groups to help guide the development of invasive species response strategies that make the best use of limited management resources. As species invasions and extinctions become increasingly interconnected, holistic approaches rooted in cumulative effects assessment and ecosystem-based management can provide a stronger foundation for reducing or mitigating this growing threat.